Improvement of student's mathematical understanding ability through problem based learning - Endang Astuty; U Usman; Bansu Irianto Ansari (SAINTIS Publishing, 2022)
The understanding mathematics ability is important for high school students. However, the reality that happened at SMAN 6 Banda Aceh, students' mathematical understanding still has not reached completeness so that it affects the final score of mathematics subjects. The cause of the problem is due to teacher-centered learning which makes learning meaningless. Therefore, a meaningful learning model is needed so that it can improve students' mathematical understanding ability. One of the meaningful learning models is the Problem Based Learning model. Based on this background, this research aims to:to find out the increase in students' mathematical understanding skills with the Problem Based Learning modelat SMAN 6Banda Aceh. This research is a quasi-experimental design with nonequivalent control group design. The research sample consisted of two classes, namely class XI IPA-2 as the experimental class consisting of 30 students with the PBL model and class XI IPA-1 as the control class consisting of 29 students with the conventional model. The data collection technique is done by test. The research instrument used is a test of mathematical understanding ability. The data analysis technique used independent sample t-test. The results showed that the value of sig. count more than sig. alpha, so it can be concluded that the increase in students' mathematical understanding through the PBL model is better than the mathematical understanding of students who get conventional learning.